Analisis Karakteristik Elektrik Onggok Singkong Fermentasi yang Diawetkan sebagai Pasta Bio-Baterai - Yuli Erviana; Amir Supriyanto; Sri Wahyu Suciyati; Gurum Ahmad Pauzi (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2020)
Bio-battery is defined as an energy storage device where the energy source comes from organic compounds. The electrical characteristics of the bio-battery can be obtained using to copper (Cu) and zinc (Zn) electrode pairs. Cassava pulp is used as the electrolyte. Cassava pulp is being fermented for 48 hours, 96 hours, and 144 hours and added 4% formalin. The electrolyte cell consists of 20 cell batteries in series with each mass is ±30 grams. The electrical characteristics of fermented cassava pulp are measured with 4 watts LED load and without load. The results show that the highest voltage is 20.66 V which is obtained by 144 hours fermented cassava pulp. The electrical characteristics in this research tend to constant due to the addition of preservatives (formalin).